Evaluation of school nutrition programme for primary school children in Batu Pahat, Johor, Malaysia - Teo, Choon Huey (2019)
Childhood malnutrition is increasing rapidly and contribute to adverse health consequences that may persist into adulthood. This quasi-experimental study aimed to evaluate the effectiveness of School Nutrition Programme (SNP) in improving knowledge, attitude and practice on nutrition, eating behaviours, physical activity, body composition, psychological distress, cognitive performance and healthy-related quality of life before the programme, after the programme and three-month follow-up after the programme between intervention and comparison groups. A total of 532 primary school children (Standard 1-5) from six selected schools (251 children from three intervention schools and 272 children from three comparison schools) in Batu Pahat District, Johor participated in this study. In the present study, the SNP consisted of two main components, namely nutrition education and healthy school food environment to improve knowledge, attitude and practice on nutrition in intervention group and facilitate them with the environment to practise healthy eating habits over a period of three months. The children in the intervention group participated in three School Nutrition Campaigns in addition to the standard Physical and Health Curriculum. The children in the comparison group received only standard Physical and Health Curriculum. School canteen food handlers were reminded to follow canteen guidelines by the Ministry of Education. All children completed anthropometric measurements and a set of selfadministered questionnaires that assessed knowledge, attitude and practice on nutrition, eating behaviours, physical activity, psychological distress and healthrelated quality of life. Cognitive performance of the children was assessed by using the Raven’s Coloured Progressive Matrices. All outcome measures were assessed at the beginning of the programme before the programme started (PreIntervention), one-week right after completing the School Nutrition Campaigns (Post-Intervention I) and after three months follow-up without intervention (Post- Intervention II), respectively. Process evaluation of the SNP comprised evaluation of the attendance rate of intervention group and programme feedback by teachers and children among the intervention group. At Pre-intervention of the study, the prevalence of thinness and stunting were 7.8% and 5.8%, respectively; whereas the prevalence of overweight and obesity were 13.4% and 16.6%, respectively. After Post-Intervention I and Post- Intervention II, the intervention group had higher knowledge, attitude and practice on nutrition, more frequent consumption of breakfast, lunch, dinner and morning tea, lower body weight and BMI-for-age (z-score), higher physical activity, higher cognitive performance and better health-related quality of life (p<0.05) as compared to the comparison group. However, no significant differences were observed in afternoon tea snacking, supper snacking, height and psychological distress between intervention and comparison groups after three months of SNP. All the teachers (100.0%) were satisfied with the SNP, and all of them were confident in delivering the nutrition education to the children. All the children (100.0%) liked the School Nutrition Campaigns. In conclusion, SNP was effective in improving knowledge on nutrition, eating behaviours, physical activity, cognitive performance and health-related quality of life and reducing BMI-for-age z-score among Batu Pahat primary school children. Hence, the SNP is highly recommended to be rolled-out to all Malaysian primary schools.